Role of active slip systems induced with holmium impurity in Bi-2212 ceramics on mechanical design performance and morphological properties - Ülgen, Asaf Tolga; Çetin, Samet; Zalaoğlu, Yusuf; Türköz, Mustafa Burak; Turğay, Tahsin (ELSEVIER SCI LTD, 2022)
Effect of Ho/Bi partial replacement in Bi2.1-xHoxSr2.0Ca1.1Cu2.0Oy (Bi-2212) superconductors on the fundamental structural, morphological and mechanical performance properties are investigated by Scanning Electron Microscopy (SEM) and Vickers hardness (Hv) measurement techniques. Crystallinity quality and surface morphology including the microcrystal coalescence orientations, grain alignment distributions, microscopic structural problems, microvoids, internal defects, uniform surface view, porosity and particle growth distribution are visually examined with the aid of SEM. Basic mechanical performance and characteristic features of Bi/Ho substituted Bi-2212 superconducting ceramics (0.00 ≤ x ≤ 0.10) are also determined with Vickers tests conducted at various loads intervals 0.245–2.940 N. Experimental findings show that the characteristic features enhance seriously in case of x = 0.01 due to refinement of crystallinity quality and slip systems. Thus, the optimum Ho concentration presents the highest mechanical fracture strength to the load applied as a result of better uniform surface appearance and grain orientations, well-connected flaky layers, larger particle size distribution and denser structure, confirmed by the SEM investigations. Namely, much more load is required to accelerate the dislocation movement and crack propagation to the terminal velocity for critical size growth. The fracture predominantly takes place in the transcrystalline regions and hence the propagations are easily controlled with the optimum Ho dopant ions. On the other hand, the increase in the Ho ions in Bi-2212 structure induces the crack-initiating defects for new stress concentration sites. In conclusion, the permanent and non-recoverable deformations appear at even lower indentation test loads. All samples present indentation size effect feature depending on the dominant character of elastic recovery mechanism. Further, original hardness parameters are semi-empirically analyzed in the plateau limit regions using mechanical modelling approaches for the first time. Based on the analyses, Hays–Kendall model exhibits the closest results to the experimental findings.
Keywords: Bi-2212 ceramic; Trivalent Ho/Bi replacement; Slip systems; Durable tetragonal phase; Mechanical modelling